2015
DOI: 10.1007/s13204-015-0456-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically retrievable nickel hydroxide functionalised AFe2O4 (A = Mn, Ni) spinel nanocatalyst for alcohol oxidation

Abstract: Ultrasmall nickel hydroxide functionalised AFe 2 O 4 (A = Mn, Ni) nanocatalyst was synthesized by traditional co-precipitation method and was examined for oxidation of aromatic alcohols to carbonyls using hydrogen peroxide as terminal oxidant. A very high surface area of 104.55 m 2 g -1 was achieved for ferromagnetic MnFe 2 O 4 and 100.50 m 2 g -1 for superparamagnetic NiFe 2 O 4 , respectively. Efficient oxidation was observed due to the synergized effect of nickel hydroxide (bronsted base) on Lewis center (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“… 38 Bhat et al reported the use of different ferrites for the oxidation of benzyl alcohol in an acetonitrile medium using H 2 O 2 as an oxidant at 80 °C for 7 h. The maximum conversion of 82.4% was attained with a nanofunctionalized NiFe 2 O 4 catalyst. 39 Nasrollahzadeh et al studied the performance of CoFe 2 O 4 NPs in the oxidation of benzyl alcohol to benzaldehyde using H 2 O 2 as an oxidant under solvent-free conditions. They acquired >99% conversion of benzyl alcohol to benzaldehyde at 110 °C for 5 h. 40 A careful investigation suggests that in the above reports either the catalyst system was prepared using a complex methodology or harsh conditions such as high temperatures or longer reaction time was applied for the desired conversion.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Bhat et al reported the use of different ferrites for the oxidation of benzyl alcohol in an acetonitrile medium using H 2 O 2 as an oxidant at 80 °C for 7 h. The maximum conversion of 82.4% was attained with a nanofunctionalized NiFe 2 O 4 catalyst. 39 Nasrollahzadeh et al studied the performance of CoFe 2 O 4 NPs in the oxidation of benzyl alcohol to benzaldehyde using H 2 O 2 as an oxidant under solvent-free conditions. They acquired >99% conversion of benzyl alcohol to benzaldehyde at 110 °C for 5 h. 40 A careful investigation suggests that in the above reports either the catalyst system was prepared using a complex methodology or harsh conditions such as high temperatures or longer reaction time was applied for the desired conversion.…”
Section: Introductionmentioning
confidence: 99%
“…With the intension to design a magnetically retrievable nanocatalyst, the same research group fabricated nickel hydroxide functionalized spinel AFe 2 O 4 (A= Mn, Ni) nanocatalyst for the oxidation of aromatic alcohols to carbonyl motifs in presence of H 2 O 2 as the oxidizing agent 161 . The motive to devote attention towards soft ferromagnetic spinel ferrites are associated with their inherent features including high dispersion, less toxicity, excellent stability, low oxidation potential values etc.…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…They observed the same trend in selectivity and conversion per unit time. Table 1 reflects the higher catalytic activity of Mn-ferrite and Ca-doped Mn-ferrite used for the oxidation of CH in solvent-free conditions compared to all reported catalysts being used for the oxidation of COH/RCOR [29][30][31]50]. Reaction progress (%) Fang & co-workers [49] performed electrocatalytic oxidation of CH to CHOH/RCOR using a functional electrocatalytic membrane reactor (ECMR) assembled with an MnO nanostructure that was loaded on a porous titanium membrane as an anode in a ternary system of CH, water and acetic acid.…”
Section: Screening Of the Catalystmentioning
confidence: 99%
“…They observed the same trend in selectivity and conversion per unit time. Table 1 reflects the higher catalytic activity of Mn-ferrite and Ca-doped Mn-ferrite used for the oxidation of CH in solvent-free conditions compared to all reported catalysts being used for the oxidation of COH/RCOR [29][30][31]50].…”
Section: Screening Of the Catalystmentioning
confidence: 99%